Fabrication of Human Genomic DNA Encapsulated Supermacroporous Alginate (SMPA) Beads - Pasandideh, Ramona (Eastern Mediterranean University - Doğu Akdeniz Üniversitesi, 2020)
In this study, human genomic DNA (hDNA) encapsulated alginate cryogel beads (SMPA) and normal alginate beads were fabricated via freeze-thawing cryogelation and microinjection procedures respectively. The fabricated beads were characterized by scanning electron microscopy (SEM) and fluorescent microscope. The characterization results showed that both beads exhibited smooth surfaces with obvious pores and burgled topologies, however, a bug-like sprout is visibly seen on the surface of SMPA beads. Also, the encapsulated hDNA showed brilliant green fluorescence when visualized with fluorescence microscopy. The encapsulation efficiency of 89.1−96.7% was achieved when the concentration of hDNA and alginate varied within 0.05−0.075% and 0.5−0.75 wt%, respectively in the presence of 0.1 M CaCl2 crosslinking agent. ~80% hDNA was released over an extended period of 80 h when SMPA was immersed in a 0.5 M Na2HPO4 solution diluted with 10 mM Tris buffer (pH 7). The SMPA cryobeads demonstrated a higher swelling capability when compared with the normal beads. In the first 3 h, SMPA cryobeads achieved 225% swelling ratio compared with the normal beads that attained 155%. Beyond 3 h, the normal beads did not show significant swelling ratio while SMPA increased obviously to 315% before reaching equilibrium at the tenth hour. iv Results and trends here demonstrated that the fabricated supermacroporous alginate-based cryogel beads have great potential to be used as a biocompatible vehicle for transporting biomacromolecules. Keywords: controlled release systems; human genomic DNA; alginate polymeric cryobeads; supermacroporous; gene therapy.

ÖZ: Bu çalışmada, insan genomik DNA'sı (hDNA) kapsüllenmiş aljinat kriyojel boncuklar (SMPA) ve normal aljinat boncuklar, sırasıyla dondurarak çözme kriyojelasyon ve mikroenjeksiyon prosedürleriyle üretildi. Üretilen boncuklar, taramalı elektron mikroskobu (SEM) ve floresan mikroskobu ile karakterize edildi. Karakterizasyon sonuçları, her iki boncuğun da bariz gözeneklere ve soyulmuş topolojilere sahip pürüzsüz yüzeyler sergilediğini, ancak SMPA boncuklarının yüzeyinde gözle görülür şekilde böcek benzeri bir filizlenme görüldüğünü gösterdi. Ayrıca kapsüllenmiş hDNA, floresan mikroskobu ile görüntülendiğinde parlak yeşil floresan ışıma göstermiştir. 0,1 M CaCl2 çapraz bağlayıcı madde varlığında hDNA ve aljinat konsantrasyonu ağırlıkça sırasıyla % 0,05 - 0,075 ve % 0,5 - 0,75 arasında değiştiğinde % 89,1 - 96,7'lik kapsülleme verimliliği elde edildi. SMPA, 10 mM Tris tamponu (pH 7) ile seyreltilmiş 0.5 M Na2HPO çözeltisi içerisinde 80 saatlik uzun bir süre boyunca bekletilmesi sonucu ortama ~% 80 oranda hDNA salınmıştır. SMPA kriyoboncukları, normal boncuklarla karşılaştırıldığında daha yüksek bir şişme kapasitesi sergiledi. İlk 3 saatte SMPA kriyoboncukları % 155'e ulaşan normal boncuklara kıyasla% 225 şişme oranına ulaştı. 3 saatten sonra, normal boncuklar önemli şişme oranı göstermezken, SMPA onuncu saatte dengeye ulaşmadan önce % 315 şişme oranına yükseldi. vi Buradaki sonuçlar ve eğilimler, üretilmiş olan süper gözenekli aljinat bazlı kriyojel boncuklarının biyomakromoleküllerin taşınması için biyo-uyumlu bir araç olarak kullanılmak için büyük bir potansiyele sahip olduğunu göstermiştir. Anahatar kelimeler: kontrollü salım sistemleri; insan genomik DNA'sı; aljinat polimerik kriyoboncuklar; süper gözenekli; gen tedavisi.
Doctor of Philosophy in Chemistry. Institute of Graduate Studies and Research. Thesis (Ph.D.) - Eastern Mediterranean University, Faculty of Arts and Sciences, Dept. of Chemistry, 202. Co-Supervisor: Assoc. Prof. Dr. Kerem Teralı and Supervisor. Prof. Dr. Mustafa Gazi.
Keywords: Controlled release systems; human genomic DNA; alginate polymeric cryobeads; supermacroporous; gene therapy